Self-Loosening Failure Analysis Considering Vibration Frequency: Experimental Study for the Spare Tire Carrier - et. al., Yohanes T. Wibowo, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The testing stage involves ensuring a product is produced correctly to achieve the targeted performance. Testing is observed from the determination of looseness resistance for a spare tire carrier to ascertain its durability due to car vibration when driven on flat and bumpy roads to avoid road users' dangers. Therefore, this study was conducted to observe the spare tire carrier's working process and analyze the changes in torque and chain tension in the drive shaft by installing a strain gauge sensor on the chain link. Moreover, the change in strain was converted into tension using mathematical calculations based on test standards. Each component of the spare tire carrier was also analyzed to determine the factors affecting chain tension changes. The results showed that the torque change on the driveshaft was 7.79%, while chain tension was 7.14% on axis 1 and 7.25% on axis 2. Therefore, the spare tire carrier passed the test with the difference not exceeding 25%, which means the road's safety aspect is guaranteed for all the users. However, the new fact is self-looseness is initiated by the vibration due to the stationary engine rotation.